Analysis of Community Satisfaction With Village Funds In Financial Management To Improve The Achievement of The Regional Development Program - Marliana, Ana (International Journal of Social Service and Research, 2021)
This research in 2021 aims to find out the Analysis of Community Satisfaction with Village Funds in Financial Management to improve the achievement of the Regional Development program in Meureubo Village, sub-district. Meureubo Kab. Aceh Barat, viewed based on community satisfaction using the Community Satisfaction Index (IKM) seen from the Village Fund. Descriptive Research is a research using analysis (IKM) Community Satisfaction Index. The research was conducted in Meureubo Village, Meureubo District with 100 respondents as the sample used. The data collected was carried out using a Questionnaire or Questionnaire method. The results showed that the community's perception of the Meureubo Village Fund, Meureubo sub-district, was seen based on Community Satisfaction using the Community (IKM) of the entire Village Fund in Financial Management to increase the achievement of regional development programs that were somewhat in line with the expectations of the community but in terms of Financial Management Slightly decreased in community satisfaction in Village development program, so with difficult conditions we see that in the future hopefully what has not been achieved, and with this research we can see how the situation of the community in Meureubo village is, how the community's satisfaction with Meureubo Village's services to the community.